Diverticular Disease of the Colon Recent Knowledge of Physiopathology, Endoscopic Approaches, Clinical and Surgical Treatments - Joaquim Ribeiro da Rocha, José; Ribeiro Feitosa, Marley (IntechOpen, 2022)
Diverticular Disease of the Colon - Recent Knowledge of Physiopathology, Endoscopic Approaches, Clinical and Surgical Treatments provides a comprehensive overview of diverticular disease. It explores general aspects of the disease as well as its association with the inflammatory process, complications, diagnosis, and treatment.